Star canoes, voyaging worlds. (3rd July 2021) - Salmond, Anne
ABSTRACT: This paper explores the realities of voyaging as understood by early Polynesian navigators. The voyaging world of Kaveia, a contemporary navigator from Outlier Polynesia, as recorded by the anthropologist sailor Mimi George, is juxtaposed with those of Tupaia and Puhoro, eighteenth century navigators from the Society Islands, to examine Polynesian understandings of the sea, canoes and islands, and how long-distance voyaging was accomplished in ancestral times. The renaissance in Polynesian voyaging is also examined, in the context of human harm to the oceanic realm, and modernist understandings of relations between people and the sea are interrogated.